2017
DOI: 10.1155/2017/5737452
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multivariate Statistical Analysis in Evaluation of Surface River Water Quality of a Tropical River

Abstract: The present study evaluated the spatial variations of surface water quality in a tropical river using multivariate statistical techniques, including cluster analysis (CA) and principal component analysis (PCA). Twenty physicochemical parameters were measured at 30 stations along the Batang Baram and its tributaries. The water quality of the Batang Baram was categorized as “slightly polluted” where the chemical oxygen demand and total suspended solids were the most deteriorated parameters. The CA grouped the 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…PCA reduces the dimensions of data by using a linear combination of variables to capture the maximum variance in the data [29][30][31]. The principal scores for each component can also be calculated, which are then used as the independent variables to build the predictive model [32][33][34] or compare it with other variables of interest [35]. The correlation matrix between the variables and the loadings of each variable in the principal components are used to investigate the contamination process in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…PCA reduces the dimensions of data by using a linear combination of variables to capture the maximum variance in the data [29][30][31]. The principal scores for each component can also be calculated, which are then used as the independent variables to build the predictive model [32][33][34] or compare it with other variables of interest [35]. The correlation matrix between the variables and the loadings of each variable in the principal components are used to investigate the contamination process in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Logging activities in the surrounding area have caused sedimentation and increased suspended solids level in the river and subsequently into the coastal area. Reference [9] demonstrated that logging was the main factor in regulating water quality of Sarawak forest streams compared to sewage discharge. In the present study, the Sarawak coastal water quality demonstrated different trend where dwellings, aquaculture, and agriculture were the major source compared to logging activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the Sarawak coastal water quality demonstrated different trend where dwellings, aquaculture, and agriculture were the major source compared to logging activities. This is most probably due to the study in [9] that was conducted in inland freshwater forest streams which were subjected to active logging activities and lower population densities. Phosphorus enrichment in Sarawak coastal water was described in PC3 and PC4 with positive loadings on IP, TP, and OP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations